Ability of Pelvic Magnetic Resonance Imaging to Predict Clinical Course of Perianal Fistula in Paediatric Crohn's Disease Patients. (7th January 2021) - Kim, Pyeong Hwa; Kim, Seo Hee; Cho, Young Ah; Yoon, Hee Mang; Lee, Jin Seong; Jung, Ah Young; Oh, Seak Hee; Kim, Dae Yeon; Namgoong, Jung-Man; Kim, Kyung Mo
Abstract: Background and Aims: Evidence is limited regarding clinical course and magnetic resonance imaging [MRI] features of perianal fistula [PAF] in Korean children with Crohn's disease [CD]. We investigated MRI features of PAF and associations with long-term outcomes. Methods: We retrospectively analysed 243 patients with pelvic MRI for diagnosis of CD. Incidence of clinically evident PAF at diagnosis was determined, as were the proportions of patients with clinical failure [failure to achieve fistula healing within 1 year] and recurrence [new/recurrent PAF after fistula healing within 1 year]. Associations between outcomes and MRI features, specified in modified Van Assche index and MAGNIFI-CD, were evaluated. Associations between later development of clinically evident PAF and subclinical PAF detected on MRI at diagnosis were evaluated. Results: Among 243 included patients, 108 [44.4%] and 76 [31.3%] had clinically evident and subclinical PAF at diagnosis, respectively; 66.4% of the patients with clinically evident PAF achieved fistula healing within 1 year, and 32.7% of those patients developed recurrence. Fistula length and dominant features of the tracts were associated with clinical failure, and fistula length was associated with recurrence. Clinically evident PAF developed in 17.0% of the patients without clinically evident PAF at diagnosis. We did not find statistically significant association between subclinical PAF and later development of clinically evident PAF [adjusted hazard ratio, 2.438; p = 0.15]. Conclusions: A considerable proportion of Korean paediatric CD patients had clinically evident and subclinical PAF. Fistula length and dominant feature of the tract on MRI are useful predictors of outcomes.